Identificação, biologia e manejo cultural do nematoide de cisto das cactáceas, Cactodera cacti - Café, Francisco Bruno da Silva (2024)
The plant-parasitic nematode Cactodera cacti has gained importance in regions where it occurs worldwide due to its detrimental effects on cactus development and its ability to form a resistant structure called a cyst, which can be easily dispersed and remain viable for years in soil without host plants. Given the potential threat of C. cacti to cacti and the scarcity of information on its biology and control, this study aimed to: 1) identify the cyst-forming nematode found in mandacaru (Cereus jamacaru) in Brazil; 2) investigate the biological aspects of the nematode, including its life cycle, number of eggs and second-stage juveniles (J2) in females and cysts, host range, J2 hatching, population multiplication, and cyst viability in soil without a host; 3) evaluate the effect of root exudates from Crotalaria juncea and C. spectabilis on J2 hatching and motility and study control methods for C. cacti in vivo using these antagonist plants. The nematode eggs, J2, or cysts used in the experiments were obtained from infected roots of dragon fruit (Hylocereus costaricensis), and the assays were conducted in a greenhouse and at the Phytopathology Laboratory/CCA/UFC. The cyst-forming nematode found in mandacaru was identified as C. cacti. In the study of its life cycle in mandacaru, cyst formation was observed 18 days after inoculation (DAI). The highest number of eggs was found in cysts at 21 and 24 DAI, and the highest number of hatched J2 was observed in cysts at 27 DAI. Only cacti served as hosts for C. cacti, and the presence of their root exudates stimulated greater J2 hatching. The nematode multiplied rapidly in dragon fruit from a single cyst, with more than 30 cysts observed after 60 days. Cyst viability for 42 months in dry soil was confirmed after new cysts were found in dragon fruit planted in the same soil. Crotalaria species did not stimulate or inhibit J2 hatching, but affected their motility and infectivity. The prior cultivation of the antagonist plants reduced C. cacti populations, and the incorporation of fresh plant matter eradicated the nematode under greenhouse conditions. This study contributed to a better understanding of C. cacti biology, clarifying important aspects related to pathogenicity, behavior, and epidemiology. Furthermore, the results demonstrated the potential effectiveness of cultural control techniques, suggesting a sustainable approach for the possible management of the nematode in the field.